The model of the Bodaibo graben formation: geological and geophysical aspects - G. A. Stogny; V. V. Stogny (Известия высших учебных заведений: Геология и разведка, 2019)
The problem of the Bodaibo graben formation has been considered within the framework of the proposed tectonic scheme of the Baikal-Patom fold belt crystalline basement — the Paleoproterozoic Baikal-Viluisk granulite-gneiss belt, which divides the foundation of the Siberian platform into Anabar-Mirninsky, Nepsko-Botuobinsky and Aldan-Stanovoi geoblocks. The Baikal-Viluisk granulite-gneiss belt is expressed by a system of blocks having a common northeastern direction and forming uplifts and grabens. As a result of the transpession interaction of the Nepsko-Botuobinsky and Anabar-Myrninsky geoblocks with Aldan-Stanovoi one in the Paleoproterozoic, the frontal part of the former was elevated with the formation of metamorphic rocks of Sarma-Tonod zone of outcrops and with the simultaneous descending of the Aldan-Stanovoi geoblock marginal part and the formation of the Olokit and Bodaibo grabens. The Olokyt graben was filled with the detrital material from the Nepsko-Botuobinsky and Anabar-Mirninsky geoblocks, and the Bodaibo graben — mainly by the products of the metamorphic rocks destruction of the Aldano-Stanovoy shield, including the gold-bearing metabasite complexes.